A cross-sectional study examining the role of doctors’ trust in patients’ requests for antibiotics: a neglected perspective - Aline Rinaldi; Serena Petrocchi; Anna Bullo; Luca Gabutti; Peter Johannes Schulz (Archives of Public Health)
Abstract Background Effective interaction between patients and providers is central to understanding communication mechanisms and health-related outcomes. Antibiotic requesting behavior and its predictors are a crucial topic in the context of antimicrobial resistance, a global health challenge that increases healthcare expenditure and negatively impacts patient outcomes. A major determinant of antibiotic misuse is rooted in primary care, where patients’ high expectations and requests, combined with doctors’ lack of assertiveness, lead to overprescription and overconsumption. Many studies report that request, as a communicative behavior, puts great pressure on doctors affecting their decision-making process. Trust is a critical aspect of this relationship that may influence both patients’ willingness to request antibiotics and doctors’ responses. This study examines how trust from the doctors’ perspective, trust from the patients’ perspective and the interaction between the two – while controlling for covariates – impact patients’ intention to ask for antibiotics, providing insights into the interpersonal dimensions that contributes to antibiotic prescribing practices. Method A cross-sectional study with 8 family doctors and 101 patients. The data gathering was performed from May to July 2024 in the Italian-speaking region of Switzerland. Post-visit questionnaires assessed trust from both parties, patients’ concerns, perceived susceptibility to illness, and symptom severity. Generalized Estimating Equations (GEE) accounted for data clustering. Results Doctors’ trust in their patients significantly reduced patients’ intentions to request antibiotics (p =.02), even when controlling for covariates. Interaction effects revealed the moderating role of doctors’ trust in shaping patients’ antibiotics requests. Discussion The results of this study highlighted the impact of doctors’ ratings of trust on patients’ intention to request antibiotics. Enhancing mutual trust in doctor-patient relationships could help reduce patient-driven antibiotic overprescription, providing a promising avenue for interventions addressing antimicrobial resistance.